2012
DOI: 10.1002/pi.4185
|View full text |Cite
|
Sign up to set email alerts
|

Control of the anisotropic morphology of latex nanocomposites containing single montmorillonite clay particles prepared by conventional and reversible addition‐fragmentation chain transfer based emulsion polymerization

Abstract: Single montmorillonite platelets have been successfully encapsulated by polymer through both a conventional and a reversible addition-fragmentation chain transfer (RAFT) based emulsion polymerization. For both synthetic methods, the encapsulation process basically consisted of three steps: (i) adsorption of cationic RAFT copolymers (RAFT approach) or surfactant (conventional approach); (ii) high shear dispersion of the stabilized clay in aqueous solutions; (iii) starved-feed addition of monomers starting the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 21 publications
0
53
0
Order By: Relevance
“…We would like to categorize the different morphologies obtained in both emulsion and miniemulsion clay encapsulation. First of all, it is noticed that the size and size distribution of the clay platelets are important parameters in the obtained morphologies, it is clearly observed that in encapsulation of a polydisperse clay different sizes of the clay are associated with different morphologies …”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…We would like to categorize the different morphologies obtained in both emulsion and miniemulsion clay encapsulation. First of all, it is noticed that the size and size distribution of the clay platelets are important parameters in the obtained morphologies, it is clearly observed that in encapsulation of a polydisperse clay different sizes of the clay are associated with different morphologies …”
Section: Resultsmentioning
confidence: 96%
“…Initially most of the work was focused on hydrophobized clay and in some cases clay with reactive groups like monomer functionalities. In the work of Voorn, it seemed that edge modification worked best to fully encapsulate the clay, later also unmodified clay was successfully encapsulated …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These hybrid materials are typically pursued for their attractive properties; some examples include the enhancement of mechanical strength of a matrix relative to the neat polymer, response to an applied magnetic field, incorporation of nanomaterials with catalytic function as well as optical properties for diagnostic imaging . The range of materials used to prepare such nanocomposites is extensive, with published examples including natural and synthetic clays, (semi‐)metal oxide nanoparticles, graphene‐derived nanosheets, carbon nanotubes, layered double hydroxides, and quantum dots . Aside from the layer‐by‐layer deposition approach, the most common method of creating such composite materials is heterophase polymerization, which encompasses emulsion, miniemulsion and dispersion polymerization .…”
Section: Introductionmentioning
confidence: 99%